2018
DOI: 10.1111/1745-9125.12189
|View full text |Cite
|
Sign up to set email alerts
|

Media Construction of Crime Revisited: Media Types, Consumer Contexts, and Frames of Crime and Justice*

Abstract: Through this study, we shed new light on a key line of inquiry for criminologists: the way the media influence the public's understanding of crime and justice. We argue for expanding the lens of studies on the media's construction of crime, moving away from one‐dimensional reactions to crime to an integrated set of frames about crime and justice policy while considering the potential influence of a diverse array of media forms and content. Most critically, this social construction process must be placed in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 95 publications
3
46
0
2
Order By: Relevance
“…First, the results suggest that Internet news consumption is negatively associated with all three criminal stereotype outcomes. This result is consistent to the growing body of work that illustrates Internet news consumption is either negatively or unrelated to attitudes associated with crime and justice (e.g., fear, punitiveness) (Baranauskas and Drakulich ; Kohm et al. ; Roche et al.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…First, the results suggest that Internet news consumption is negatively associated with all three criminal stereotype outcomes. This result is consistent to the growing body of work that illustrates Internet news consumption is either negatively or unrelated to attitudes associated with crime and justice (e.g., fear, punitiveness) (Baranauskas and Drakulich ; Kohm et al. ; Roche et al.…”
Section: Discussionsupporting
confidence: 88%
“…Third, similar to many previous assessments on Internet news and public opinion, our study did not collect information on contextual measures (e.g., neighborhood conditions, crime rate, racial composition). For example, a recent assessment by Baranauskas and Drakulich () found that media effects are dependent on the racial composition of consumers’ neighborhoods. Using multiple nationally representative samples, the authors found that among white respondents, the effect of television news and crime drama viewership increased perceptions of crime among those who live near a large number of African Americans, suggesting that “people interpret crime news within the racial context of their own neighborhoods” (Baranauskas and Drakulich :28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations